Brain oscillations in cognitive control: A cross-sectional study with a spatial stroop task. (October 2019) - Tafuro, Alessandra; Ambrosini, Ettore; Puccioni, Olga; Vallesi, Antonino
Abstract: An important aspect of cognitive control is the ability to overcome interference, by boosting the processing of task-relevant information while suppressing the irrelevant information. This ability is affected by the progressive cognitive decline observed in aging. The aims of this study were to shed light on the neural spectral dynamics involved in interference control and to investigate age-dependent differences in these dynamics. For these reasons two samples of participants of different ages (23 younger and 20 older adults, age range = [18 35] and [66 82], respectively) were recruited and administered a spatial Stroop task while recording electroencephalographic activity. Scalp- and source-based time-frequency analyses revealed a main role of theta and beta frequencies in interference control. Specifically, for the theta band, we found age-dependent differences both for early event-related spectral perturbation (ERSP) Stroop effects at the source level – which involved dorsomedial and dorsolateral prefrontal cortices – and for related brain-behaviour correlations. This ERSP Stroop effect in theta was greatly reduced in magnitude in the older group and, differently from what observed in younger participants, it was not correlated with behavioural performance. These results suggest an age-dependent impairment of the theta-related mechanism signalling the need of cognitive control, in line with existing findings. We also found age-related differences in ERSP and source spectral activity involving beta frequencies. Indeed, younger participants showed a specific ERSP Stroop effect in beta – with the main involvement of left prefrontal cortex – whereas the pattern of older participants was delayed in time and spread bilaterally over the scalp. This study shows clear age-related differences in the neural spectral correlates of cognitive control. These findings open new questions about the causal involvement of specific oscillations in different cognitive processes and may inspire future interventions against age-related cognitive decline. Highlights: We studied spectral correlates of interference control in younger and older participants. We found clear scalp and source-based group differences in midfrontal theta and prefrontal beta bands. Theta band marking the need of cognitive control was reduced in older adults. Beta activity was increased in older adults, in line with age-related dedifferentiation theories.